Bending of Fragmented Architraves Restored With Bolted Titanium Bars: a Numerical Analysis - KOURKOULIS, S. K.; GANNIARI-PAPAGEORGIOU, E. (Engineering Transactions, 2014)
The mechanical behaviour of restored structural members of ancient monuments is studied in the present paper with the aid of the Finite Element Method. The study is motivated by the needs of the conservation project in progress on the Parthenon Temple of the Acropolis of Athens; the results however could be valuable for various stone monuments under conservation. Centrally fractured prismatic marble architraves (epistyles) of rectangular cross-section restored with either threaded or smooth titanium bars are modelled. The architraves are resting on marble blocks simulating the capitals (abacuses) of the columns of the temple. They are subjected to bending under uniformly distributed loading along their span, following the results of earlier studies, concerning the influence of the loading mode on the overall behaviour of restored structural members. The method used for determination of the reinforcement required is the one introduced recently by the scientists working for the restoration of the Acropolis monuments. All the loads that could be applied on the member after it is replaced in its initial position in the monument were taken into account, including the own weight of the member, the weights of the members that will rest on it after the restoration, as well as possible dynamic (earthquake) loads. Emphasis is laid on the influence of the threads of the bolted bars in comparison to the results for the unbolted ones, in an effort to quantify the maximum anchoring length required in order to minimize the intervention on the authentic stones. The distribution of the stress and strain fields all over the architrave-abacus-reinforcing bar system is investigated and conclusions are drawn concerning the extreme stresses and the points where they are developed.